EVALUATION OF THE POSITION OF THE MANDIBULAR CONDYLE ON CBCT - Silvia Izabella Pop; Laura-Roxana Contac; Mariana Păcurar; Alexandru Meroiu; Raluca Irofte; Mihai Mițaru; Radu Vasile Pop (Romanian Society of Oral Rehabilitation, 2023)
Objectives: The objective of this study is to evaluate, by means of CBCT Cone Beam CT examination, the correlation between the position of the mandibular condyle and the type of orthodontic anomaly. Materials and Methods: Twenty patients of the Natural Smile Clinic in Târgu-Mureș were included in this study, and their 8×15 FOV CBCTs were evaluated. The patients were selected according to the following criteria: age (6-18 years, 18-40 years, respectively 40-70 years), sex (men, women), facial pattern (hyperdivergent, normodivergent, hypodivergent), skeletal class (I, II ). The temporomandibular joint was divided into two sections (sagittal and transverse), measuring 4 parameters: anteroposterior (AP), superior (S), medial (M) and lateral (L), in this order, then performing comparative measurements using CBCT. Results: Differences between mandibular condyle positions were not statistically significant between males vs females, but a significant difference (P≤05) was recorded for the right condyle in all other categories (age, skeletal class, facial pattern). Most measurements in the sagittal plane indicated a statistically significant difference in the anteroposterior parameter, as well as the lateral one. In the case of the left condyle, a single measured item recorded a statistically significant value, comparing the age groups 6-18 years with 40-70 years. Conclusions: Statistically significant differences in condylar positions were identified between age groups, skeletal class and facial pattern, but there were no statistically significant differences between males and females.